Caffeine Protects Against Retinal Inflammation - Conti, Federica; Lazzara, Francesca; Romano, Giovanni Luca; Platania, Chiara Bianca Maria; Drago, Filippo; Bucolo, Claudio (Frontiers in Pharmacology, 2022)
Caffeine, one of the most consumed central nervous system (CNS) stimulants, is an antagonist of A1 and A2A adenosine receptors. In this study we investigated the potential protective effects of this methylxanthine in the retinal tissue. We tested caffeine by using in vitro and in vivo paradigms of retinal inflammation. Human retinal pigmented cells (ARPE-19) were exposed to lipopolysaccharide (LPS) with or without caffeine. This latter was able to reduce the inflammatory response in ARPE-19 cells exposed to LPS, attenuating the release of IL-1, IL-6, TNF- and the nuclear translocation of p-NFκB. Additionally, caffeine treatment restored the integrity of ARPE-19 monolayer assessed by trans endothelial electric resistance (TEER) and sodium fluorescein permeability test. Finally, the ischemia reperfusion (I/R) injury model was used in C57BL/6J mice to induce retinal inflammation and investigate the effects of caffeine treatment. Mouse eyes were treated topically with caffeine and pattern electroretinogram (PERG) was used to assess the retinal ganglion cells (RGCs) function; furthermore, we evaluated the levels of IL-6 and BDNF in the retina. Retinal BDNF dropped significantly (p<0.05) in the I/R group compared to the control group (normal mice); on the contrary, caffeine treatment maintained physiological levels of BDNF in retina of I/R eyes. Caffeine was also able to reduce IL-6 mRNA levels in the retina of I/R eyes. In conclusion, these findings suggest that caffeine is a good candidate to counteract inflammation in retinal diseases.